1992
DOI: 10.1097/00000658-199208000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Cholecystectomy in the Obese Patient

Abstract: The authors' experience with laparoscopic cholecystectomy (LC) in obese (O, n = 96) and morbidly obese (MO, n = 27) patient groups was compared with that in the normal weight (NW, n = 174) group of patients as well as the whole group (WG). There were no operative deaths. There were no significant differences between groups for any of the following: successful intraoperative cholangiography (WG, 52.2%; NW, 52.9%; O, 51.1%; MO, 55.6%), conversion to open cholecystectomy (WG, 9.6%; NW, 9.2%; O, 10.4%; MO, 11.1%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(26 citation statements)
references
References 10 publications
0
25
0
1
Order By: Relevance
“…Obesity is known to make access to the peritoneal cavity difficult, thus necessitating conversion to open laparotomy. 12,13 In this study 68% had BMI≀30, and 32% patients were having BMI>30, but there was no significant difference in obese patients with regard to conversion rates and operative time (p>0.05).The reason for higher conversion rates in male patients remains unexplained, though male gender has been a significant risk factor in most series. 8,14 It has been observed that male patients have more intense inflammation or fibrosis, resulting in more difficult dissection both in the triangle of Calot's and through the plane between the GB and the liver.…”
Section: Discussionmentioning
confidence: 56%
“…Obesity is known to make access to the peritoneal cavity difficult, thus necessitating conversion to open laparotomy. 12,13 In this study 68% had BMI≀30, and 32% patients were having BMI>30, but there was no significant difference in obese patients with regard to conversion rates and operative time (p>0.05).The reason for higher conversion rates in male patients remains unexplained, though male gender has been a significant risk factor in most series. 8,14 It has been observed that male patients have more intense inflammation or fibrosis, resulting in more difficult dissection both in the triangle of Calot's and through the plane between the GB and the liver.…”
Section: Discussionmentioning
confidence: 56%
“…In fact, findings have shown that obesity does not increase surgical morbidity during several simple laparoscopic procedures, such as laparoscopic cholecystectomy [22]. Furthermore, some researchers have insisted that a laparoscopic approach should be the preferred method for obese patients with these procedures [23].…”
Section: Discussionmentioning
confidence: 99%
“…There were difficulties associated with abdominal entry, insufflations of the obese abdominal wall, ventilation when positioning the patient in Trendelenburg and visualization secondary to increased intra-abdominal fat. General surgeons shared this sentiment at the time [5] and also considered obesity to be a contra indication. Interestingly, even today, 98% of Canadian surgeons believe that obesity increases operative time for colonic procedures [6].…”
Section: Editorialmentioning
confidence: 97%